Primary lung cancer presenting with metastasis to the colon: a case report - Sakai, Hiroshi (BioMed Central, 2012)
Although about 50% of lung cancers have distant metastasis at the time of initial diagnosis, colonic metastases are extremely rare. This report presents a rare clinical case of colonic metastasis from primary squamous cell carcinoma of the lung. A 60-year-old female with anorexia and fatigue was referred to the department of pulmonary surgery in our hospital. The patient was diagnosed with primary squamous cell carcinoma of the lung, T2b N3 M1b Stage IV, and chemoradiotherapy was initiated. This treatment led to a good partial response in the primary lung lesion without any new metastatic lesions. The patient developed left abdominal pain due to a bulky sigmoid colon tumor 6 months later, and was preoperatively diagnosed with primary colon cancer. She underwent colonic resection, and the pathology specimen demonstrated poorly differentiated squamous cell carcinoma that was suspected to be colonic metastasis from the primary lung cancer. The postoperative course was uneventful, and she was discharged. Chemotherapy for the lung cancer was scheduled in the department of pulmonary surgery. This report presented a rare case of colonic metastasis from lung cancer. When patients with advanced primary lung cancer complain of abdominal symptoms, we should consider gastrointestinal tract metastasis from lung cancer.